Non-coding RNAs in skin cancers:Biological roles and molecular mechanisms - Liu, Fei; Li, Shenglong (Frontiers in Pharmacology, 2022)
Cutaneous malignancies, including basal cell carcinoma, cutaneous squamous cell carcinoma, and cutaneous melanoma, are common human tumors. The incidence of cutaneous malignancies is increasing worldwide, and the leading cause of death is malignant invasion and metastasis. The molecular biology of oncogenes has drawn researchers’ attention because of the potential for targeted therapies. Noncoding RNAs, including microRNAs, long noncoding RNAs, and circular RNAs, have been studied extensively in recent years. This review summarizes the aspects of noncoding RNAs related to the metastasis mechanism of skin malignancies. Continuous research may facilitate the identification of new therapeutic targets and help elucidate the mechanism of tumor metastasis, thus providing new opportunities to improve the survival rate of patients with skin malignancies.